Electronic Resource Management Systems - Ellingsen, Mark (LIBER Quarterly: The Journal of the Association of European Research Libraries, 2004)
Computer applications which deal with electronic resource management (ERM) are quite a recent development. They have grown out of the need to manage the burgeoning number of electronic resources particularly electronic journals. Typically, in the early years of e-journal acquisition, library staff provided an easy means of accessing these journals by providing an alphabetical list on a web page. Some went as far as categorising the e-journals by subject and then grouping the journals either on a single web page or by using multiple pages. It didn’t take long before it was recognised that it would be more efficient to dynamically generate the pages from a database rather than to continually edit the pages manually. Of course, once the descriptive metadata for an electronic journal was held within a database the next logical step was to provide administrative forms whereby that metadata could be manipulated. This in turn led to demands for incorporating more information and more functionality into the developing application.